Recent advances in understanding of the mechanism of paraquat resistance - Visnovitz, Tamás (Acta Biologica Szegediensis, 2008)
Cationic amino acid/polyamine transporter CAT4 is supposed to play essential part in paraquat resistance of horseweed. In order to get better understanding on its role in resistance mechanism here we examined and compared the expression level of this transporter in the susceptible rape Brassica napus and in the different (susceptible and resistant) biotypes of horseweed. We found that paraquat induced an increase in expression level of CAT4 in rape, similarly to its upregulation in horseweed.